PENGARUH KESADARAN WAJIB PAJAK, SOSIALISASI PAJAK, PENERAPAN E-FILING, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Putri Noer Fadhilah; Nyimas Wardatul Afiqoh (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to determine the Effect of Taxpayer Awareness, Tax Socialization, Implementation of e-Filing, and Tax Sanctions on Individual Taxpayer Compliance. This study used 88 respondents. This research approach uses a quantitative approach, the source of data in this study is primary data and the type of data is subject data. Using multiple linear regression analysis method. Hypothesis testing was carried out using the F test and t test to determine the effect of the independent variable on the dependent variable. The results of this study indicate that the taxpayer awareness variable has a positive and significant effect on individual taxpayer compliance, the tax socialization variable has a positive and significant effect on individual taxpayer compliance, the application of e-filing has no effect on individual taxpayer compliance, and tax sanctions. does not affect the compliance of individual Taxpayers.